2004
DOI: 10.1007/s00264-004-0574-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personality traits on the subjective outcome of operative hallux valgus correction

Abstract: We studied prospectively the influence of personality traits on the subjective outcome of a chevron osteotomy in 42 patients with hallux valgus. The mean age of patients was 48.3 (20-70) years. Personality traits were evaluated by the means of the Freiburg Personality Inventory (FPI-R). Three months postoperatively 37 patients were satisfied, and five patients not satisfied with the operative procedure. The preoperative AOFAS Score improved from an average of 48.7 (30-65) points to 87.9 (50-100) points. A com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…There is general agreement that psychological factors such as personality may influence patients' adjustment and outcome of surgical interventions [7,8]. For example, dissatisfied patients were characterized by significantly higher aggressiveness, lower extraversion, and more health worries compared to satisfied patients without differences in hallux valgus angle or intermetatarsal angle (I-II) three month after operative hallux valgus correction [9]. In another study, Hyphantis et al [10] reported that arthritis-related pain and hostility were negatively related to both physical as well as psychological health in patients suffering from systemic sclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…There is general agreement that psychological factors such as personality may influence patients' adjustment and outcome of surgical interventions [7,8]. For example, dissatisfied patients were characterized by significantly higher aggressiveness, lower extraversion, and more health worries compared to satisfied patients without differences in hallux valgus angle or intermetatarsal angle (I-II) three month after operative hallux valgus correction [9]. In another study, Hyphantis et al [10] reported that arthritis-related pain and hostility were negatively related to both physical as well as psychological health in patients suffering from systemic sclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Over 130 different surgical techniques [1][2][3][4] to correct hallux valgus deformity have been proposed, although choosing the most appropriate treatment option continues to generate controversy [5][6][7][8][9][10][11]. The current trend is directed toward percutaneous procedures with the potential benefits of minimally invasive surgery [2], e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The decision to operate and which technique to apply depends on the severity of the deformity [1][2][3][4][5] Table 1.…”
Section: Introductionmentioning
confidence: 99%